Beneficial Effects of Alhagi Plant on Liver Health and its Anti-Inflammatory Properties - D. B, Khaydarov (American Journal of Biomedicine and Pharmacy, 2025)
The liver plays a crucial role in detoxifying harmful substances and managing metabolic processes in the body. Inflammation is a significant factor contributing to liver disorders. Traditionally, the Alhagi plant has been used to support liver function and treat related ailments. This article reviews the chemical composition of Alhagi, its benefits for liver health, and its ability to reduce inflammation.